Coal-fired generation - Breeze, Paul (London : Academic Press is an imprint of Elsevier, 2015)
Coal-Fired Generation is a concise, up-to-date and readable guide providing an introduction to this traditional power generation technology. It includes detailed descriptions of coal fired generation systems, demystifies the coal fired technology functions in practice as well as exploring the economic and environmental risk factors. Engineers, managers, policymakers and those involved in planning and delivering energy resources will find this reference a valuable guide, to help establish a reliable power supply address social and economic objectives.
Carbon Dioxide Sequestration8 The Cost of Electricity Generation from Coal-Fired Power Stations; Capital Cost; Fuel Costs; The LCOE from a Coal-Fired Power Station
Includes bibliographical references.
Online resource; title from PDF title page (EBSCO, viewed July 24, 2015).
Elsevier
Keywords: Coal-fired power plants; Coal -- Combustion; Electric power production; TECHNOLOGY & ENGINEERING / Mechanical; Coal mines and mining; Coal mines and mining--United States--Forecasting.; Coal reserves--United States--Forecasting.; Coal -- Combustion; Coal-fired power plants; Electric power production; Electronic books; Electronic books